Mekanisme Pembentukan Perda Pendidikan di Tanah Datar: ‎Studi Pasal 51 tentang Pendidikan Pemberdayaan ‎Perempuan/Bundo Kanduang - Fadila Ramadhan (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The preparation of Regional Regulations (Perda) in the field of education in Tanah Datar ‎Regency involves structured and systematic stages, starting from planning to evaluation. ‎This process aims to address the challenges and needs of the education sector in the ‎region, as well as improve the quality of education through clear policies. The ‎preparation of the Draft Regional Regulation is carried out by a joint team from related ‎agencies and involves a harmonization and verification process before being ratified by ‎the DPRD. Socialization of the Regional Regulation is carried out to ensure that the ‎community understands and can implement this policy properly. Evaluation is carried ‎out to assess the effectiveness of the implementation of the Regional Regulation and ‎identify existing obstacles. One of the important aspects of this Regional Regulation is ‎Article 51, which regulates women's empowerment, especially the role of Bundo ‎Kanduang, in increasing women's participation in education and regional development. ‎Overall, this Regional Regulation is expected to have a positive impact on the education ‎sector and women's empowerment in Tanah Datar Regency, by prioritizing the ‎principles of equality and inclusivity in development.‎